2015
DOI: 10.1177/0022427815593988
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Maternal Incarceration on the Criminal Justice Involvement of Adult Offspring

Abstract: Objectives: This note examines the relationship between maternal incarceration and adverse outcomes for offspring in early adulthood. Methods: Utilizing data derived from the National Longitudinal Survey of Adolescent Health, a series of multivariate models are conducted to examine the impact maternal incarceration has on criminal justice involvement among young adults. To control for selection effects that may be associated with maternal imprisonment, propensity score matching is utilized. Results: Respondent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…Further, Murray et al (2007) found women with incarcerated parents were more at risk of offending than men. Muftic, Bouffard, and Armstrong (2016) suggest the consequences of parental incarceration may be different based on paternal and maternal incarceration. For instance, Grant (2006) found maternal incarceration was negatively associated with young girls' self-perceptions, while found internalizing symptoms were higher for daughters of incarcerated mothers.…”
Section: Parental Incarceration For Womenmentioning
confidence: 99%
“…Further, Murray et al (2007) found women with incarcerated parents were more at risk of offending than men. Muftic, Bouffard, and Armstrong (2016) suggest the consequences of parental incarceration may be different based on paternal and maternal incarceration. For instance, Grant (2006) found maternal incarceration was negatively associated with young girls' self-perceptions, while found internalizing symptoms were higher for daughters of incarcerated mothers.…”
Section: Parental Incarceration For Womenmentioning
confidence: 99%
“…[16], for example, observed the growth in female incarceration to further understand the long-term consequences of imprisonment on children. Their research utilized data derived from the National Longitudinal Survey of Adolescent Health to examine the impact maternal incarceration has on criminal justice involvement among young adults.…”
Section: Maternal Incarceration and Problem Behaviormentioning
confidence: 99%
“…Their research utilized data derived from the National Longitudinal Survey of Adolescent Health to examine the impact maternal incarceration has on criminal justice involvement among young adults. The key findings demonstrated that maternal incarceration had a statistically significant effect on the children's adult involvement in the criminal justice system, which was measured by arrest, conviction, and incarceration [16]. [10] Examined serious delinquency among youth and the associations between parental incarceration, family functioning, parental health, effective parenting, and youth problems.…”
Section: Maternal Incarceration and Problem Behaviormentioning
confidence: 99%
See 2 more Smart Citations